The role of non-governmental organizations in strengthening healthcare systems in low- and middle-income countries: Lessons from Santé Diabète in Mali - Stéphane Besançon; Assa Sidibé; Djeneba Sylla Sow; Ousmane Sy; Julien Ambard; John S. Yudkin; David Beran (Global Health Action, 2022)
Non-governmental organizations play a vital part in the achievement of the Sustainable Development Goals as defined by the United Nations. These Goals also include targets related to noncommunicable diseases. However, non-governmental organizations have played a limited role in this area despite such diseases causing the bulk of morbidity and mortality worldwide. Through their activities, non-governmental organizations should aim to strengthen health systems, yet they often only support these for a single disease. Mali, like many other low- and middle-income countries, is facing an increasing burden of diabetes and a health system not adapted to address this challenge. Santé Diabète, a non-governmental organization based in Mali since 2003, has been working specifically on diabetes, and has developed a wide range of activities to improve the national health system. This paper describes changes in the diabetes environment in Mali between 2004 and 2018 based on two health system assessments carried out using a Rapid Assessment Protocol. Over this period, the health system was strengthened with regard to financing and access to medical products. Leadership and governance, service delivery and health workforce were all improved but still partially rely on sustained support from Santé Diabète. The key lesson from this study is that to be effective in changing the management of noncommunicable diseases in a low- and middle-income country, non-governmental organizations need to play a variety of roles, many of which may change over time.